Development of Augmented Reality-based Arabic Uslub Materials to Improve Daily Language Expressing Ability - Hasaniyah, Nur; Arsyad, Berti; A. Hasan, Adtman (ELOQUENCE : Journal of Foreign Language, 2023)
Background: A language is a communication tool every person uses to express their desires. However, few students who learn Arabic find it challenging to speak the daily language with the correct uslub Objective: This study aims to develop the Arabic language based on Augmented Reality to improve the ability to express with the correct phrasing and diverse language styles. Method: This study used the RnD method with the ADDIE model. The research location is at the IAIN Sultan Amai Gorontalo Language Development Center. The population is 100 students, and the sample is 30 students. The data collection procedure is done by observation, interview, lift and test. Data analysis techniques are carried out with T-tests, and presentations are carried out with Likert scales. Results and Discussion: This study produced several recommendations that the basis of Augmented Reality can improve students' ability to express Arabic with the correct uslub Conclusion and Implication: This study concluded that students' ability to express themselves with the Arabic language needs to be accompanied, trained and continue to be familiarized with campus life so that daily expressions become spontaneous habits. The implications of this study suggest that learning Arabic using standard terms can be helped by augmented reality as a technology that combines digital elements, such as images, sounds, and virtual objects, with user needs.